2002
DOI: 10.1002/ajmg.10261
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the dup5q phenotype by molecular cytogenetic analysis in a patient with dup5q/del 5p (cri du chat)

Abstract: An infant girl presented with multiple congenital abnormalities and a distinctive mewing cry. Her karyotype was 46,XX,add5p. Chromosome analysis on the mother revealed an apparently balanced pericentric inversion of chromosome 5, with the precise position of the breakpoints not clearly discernable by GTG banding, 46,XX,inv(5)(p15.2/3?q35.1?). Fluorescence in situ hybridization (FISH) studies using a commercial cri du chat probe (D5S721,D5S23) revealed signals on both the normal and derivative chromosomes. Telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…This finding suggests that one or more genes located within the duplicated region are sensitive to dosage alterations influencing brain development. Clinical features commonly reported among 32 clinically well-described patients with microscopically visible duplications spanning cytoband 5q35.1 are low birth weight, developmental delay, mental retardation, microcephaly, down-turned palpebral fissures, hypertelorism, micrognathia, dysplastic ears and congenital heart defects (Groen et al 1998;Lazjuk et al 1985;Levy et al 2002;Rodewald et al 1980;Schinzel 2003;Schroeder et al 1986). HPE was reported in two cases: a girl with a duplication of 5q32 fi qter [46,XX,der(10)t(5;10)(q31.3;q26)] and a boy with a microscopically visible 5q32->qter duplication and a 5p15 fi pter deletion, due to an inversion [46,XY, rec(5), dup q, inv(5)(p15q32)] (Lazjuk et al 1985;Schroeder et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that one or more genes located within the duplicated region are sensitive to dosage alterations influencing brain development. Clinical features commonly reported among 32 clinically well-described patients with microscopically visible duplications spanning cytoband 5q35.1 are low birth weight, developmental delay, mental retardation, microcephaly, down-turned palpebral fissures, hypertelorism, micrognathia, dysplastic ears and congenital heart defects (Groen et al 1998;Lazjuk et al 1985;Levy et al 2002;Rodewald et al 1980;Schinzel 2003;Schroeder et al 1986). HPE was reported in two cases: a girl with a duplication of 5q32 fi qter [46,XX,der(10)t(5;10)(q31.3;q26)] and a boy with a microscopically visible 5q32->qter duplication and a 5p15 fi pter deletion, due to an inversion [46,XY, rec(5), dup q, inv(5)(p15q32)] (Lazjuk et al 1985;Schroeder et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Since the propositus did have a characteristic high-pitched cry and speech delay, the phenotype was well correlated with the genotype. The duplicated region, 5q34-5qter, recapitulates the duplicated interval reported by Levy et al [2002], who suggested that the characteristic features that can be ascribed to this region include a prominent forehead and a bulbous nose. Because the report by Levy et al lacked a facial photograph, a direct comparison of these features is not possible.…”
Section: Resultsmentioning
confidence: 75%
“…This combination is virtually always associated with parental large pericentric inversions that lead to the formation of an inversion loop, promoting the production of double segmental aneusomy or meiotic recombination aneusomy in the gametes [de Perdigo et al, 1989]. Among previously reported cri-du-chat syndrome cases with meiotic recombination, the aneusomy of chromosome 5 in all [Faed et al, 1972;Neibuhr, 1978;Beemer et al, 1984;Miyazaki et al, 1985;Schroeder et al, 1986;Sonoda et al, 1989;Ono et al, 1993;Levy et al, 2002] but one case [Akalin et al, 2006] was cytogenetically visible using G-banding. When an accompanying 5q trisomy is detected, a significant recurrence risk is expected [Anton et al, 2005].…”
mentioning
confidence: 99%
“…Conventional CGH is also a reliable technique for detecting structural aberrations, and in specific cases, may be more efficient in diagnosing complex abnormalities than karyotyping (8). However, conventional CGH is unable to detect mosaicism, balanced chromosomal translocation, inversions, and wholegenome ploidy changes (9).…”
Section: Conventional Cghmentioning
confidence: 99%